Effect of extrusion on phytochemical profiles in milled fractions of black rice. (1st July 2015) - Ti, Huihui; Zhang, Ruifen; Zhang, Mingwei; Wei, Zhencheng; Chi, Jianwei; Deng, Yuanyuan; Zhang, Yan
Highlights: Free & bound phytochemicals in milled fractions of black rice exist differences. The changing ranges of free & bound phytochemicals varied after extrusion. Extrusion slightly increases the release of phytochemicals in black rice bran fraction. Extrusion causes significant phytochemical loss in polished/brown rice fractions. Free fractions contributes most to total phytochemicals before and after extrusion. Abstract: The phytochemical profile and antioxidant activities of unprocessed and extruded milled fractions of black rice were investigated. Extrusion increased the free phenolics, anthocyanins and oxygen radical absorbance capacity (ORAC) and decreased the bound forms. The total phenolics, anthocyanins and ORAC increased by 12.6%, 5.4% and 19.7%, respectively, in bran. Extrusion decreased both free and bound phenolics and anthocyanins while ORAC values decreased by 46.5%, 88.4% and 33.1%, respectively, in polished rice and by 71.2%, 87.9% and 14.7%, respectively, in brown rice. A total of seven phenolics, gallic, chlorogenic, vanillic, caffeic, syringic, p -coumaric and ferulic acids, were detected in both forms. Cyanidin 3-glucoside (Cy-3-G), cyanidin 3-rutinoside and peonidin 3-glucoside were also detected with Cy-3-G found in the highest amounts in unprocessed and extruded rice bran. These results provide the basis for the development of different milled fractions of extruded black rice with balanced nutritional characteristics for today's functional food markets.